PERAN BUDAYA ORGANISASI DALAM MENDORONG KEPATUHAN TERHADAP REGULASI HUKUM DI LINGKUNGAN KERJA ERA DIGITALISASI - Nurhasanah Nurhasanah; Babby Apriandani; Julpan Hartono Suria Manja Manurung; Rizky Ayu (Smart Education, 2026)
Abstract: This study employs a quantitative approach with an explanatory research design to examine the causal relationship between the variables under investigation. Data were collected from respondents via questionnaires serving as the primary data source and subsequently analyzed using the Statistical Package for the Social Sciences (SPSS) software. The study population consisted of currently active teachers at SMK Swasta Amal Bakti. Sampling was conducted using a non-probability sampling technique specifically purposive sampling whereby respondents were selected based on predetermined criteria. The t-test results in the